Strategi Pick Up Service dalam Meningkatkan Minat Menabung Studi Pada KSSU Harum Dhaha Kediri Perspektif Marketing Syariah - Isneyni Robi’ul Laila; Adin Fadilah (Sharia Business Management Study Program, Faculty of Economics and Islamic Business at IAIN Kediri, 2023)
Koperasi Syariah Serba Usaha (KSSU) Harum Dhaha Kediri in its operations has financing products and savings products. The changing times have an impact on the behavior of people today who want to save but don't have time because of their busyness. So that KSSU Harum Dhaha Kediri applies Pick Up Service, in order to help busy members keep saving so that member interest can increase. The purpose of this study was to determine the Pick Up Service Strategy in increasing the interest in saving members of KSSU Harum Dhaha Kediri from Sharia Marketing. This research uses a qualitative approach with descriptive research type. Data collection using observation, interview, and documentation methods. The data sources of this research are directors, employees, and members of KSSU Harum Dhaha Kediri. Checking the validity of the data with techniques of extension of participation, persistence of observation, and triangulation. The results of this study indicate in increasing interest in saving members at KSSU Harum Dhaha Kediri using the Pick Up Service strategy, the strategy of convenience in transactions without having to come to the office. This cooperative, using a family approach by applying aspects of the marketing mix to create the characteristics of the services offered. While the Pick Up Service strategy in increasing the interest in saving members at KSSU Harum Dhaha Kediri in terms of Sharia Marketing is appropriate.